COMPARATIVE EVALUATION OF THE PERIODONTAL STATUS AND SERUM PARAMETERS IN NORMAL BODY MASS INDEX AND OBESE CHILDREN - Amelia Surdu; Daniela Trifan; Irina-Georgeta Sufaru; Oana Cristina Cretu; Mihaela Monica Scutariu (Romanian Journal of Oral Rehabilitation)
Objective: Childhood obesity is a growing global health concern, with established associations to both systemic and oral health complications. This study aimed to compare periodontal status and inflammatory biomarkers between obese and non-obese children. Materials and methods: Fifty-two children (26 obese, 26 non-obese) were included, with key parameters such as Plaque Index (PI), Bleeding on Probing (BOP), Probing Depth (PD), and Clinical Attachment Loss (CAL) assessed to evaluate periodontal health. Paraclinical indicators including fibrinogen, C-reactive protein (CRP), and vitamin D (25(OH)D) levels were also measured. Results and Discussion: Results demonstrated that obese children exhibited significantly higher values for PI, BOP, PD, and CAL, indicating poorer periodontal health. Elevated serum fibrinogen and CRP levels, coupled with lower vitamin D levels in obese children, underscored a state of chronic inflammation and potential nutrient deficiency associated with obesity. Conclusion: These findings highlight the need for a multidisciplinary approach to managing obesity and promoting oral health, suggesting that early intervention in dietary and lifestyle factors could mitigate these risks.